Policies and Background Literature for Self- Education on Research Data Management: An Annotated Bibliography. - Goben, Abigail; Raszewski, Rebecca (Issues in Science and Technology Librarianship, 2015)
This annotated bibliography reviews U.S. federal policies, articles, and books to assist librarians who are self-educating on research data management or are seeking background reading material to gain insight into the present landscape of data management and librarianship.